(untitled) (Research, Society and Development, 2020)
Upon arriving in another country, refugees undergo an adaptation process. Oral health has important aspects in relation to integral health and social issues. Considering the refugee’s difficulties, this work was developed to present the development of an accessible and objective primer on oral health to this population. Initially, the content was selected covering five topics: Oral hygiene instructions, Hygiene with the use of dental prosthesis, Oral care for pregnant women, Oral care for babies and children and Oral cancer. And, information about access to routine dental care and emergencies were included. Subsequently, the information was presented in a simple way and by means of images that are representative for these populations. Finally, naturalized refugees adapted terminologies and translated this material into five languages: French, English, Spanish, Creole and Arabic. Regarding the importance of primary care, the primer is a fundamental tool for refugees. It is an important resource for health education and information on ways to access health services.